OS DESAFIOS DO ESTÁGIO PROFISSIONAL: A IMPORTÂNCIA DA MOTIVAÇÃO E DA SOCIALIZAÇÃO NAS AULAS DE EDUCAÇÃO FÍSICA. - Anderson Santos da Silva (2023)
This document expresses the reflections and pedagogical actions adopted by me during the training process, in relation to the School Placement of the 2nd cycle of studies, leading to a Master's degree in Physical Education Teaching in Basic and Secondary Education, carried out at the António Nobre Secondary School, which is located in the district of Porto, and qualifies as an educational institution that promotes training offers related to the 3rd Cycle of schooling, Secondary Education, Regular and also Vocational. The aim of this report is to analyze, study and understand the importance of the teaching and learning process during the physical education lessons of the 12th year of the Scientific-Humanistic Course in Science and Technology, especially regarding the motivational factors that lead students to get involved in the proposed tasks, as well as the interference of this theme with socialization. The central theme highlights the particularities and challenges of the supervised School Placement experience, to promote reflection on the interactions of the teacher-student relationship in class. The experience of the School Placement transformed my life, helping me to move into the profession in a gradual and significant way for my future teaching career, since it promoted the construction of important reflections, such as the importance of a favorable environment for learning; the role of the teacher as a facilitator of the process and the management of the planning, organization and teaching of physical education classes, in order to promote the construction of knowledge. The study of the topics covered in the problem indicates that a school environment with a high level of motivation positively interferes with involvement in the proposed tasks and favors the process of socialization in class, and that the student teacher must incessantly search for new knowledge and must adapt to the different interests that motivate students to participate in their classes.